Being Holistic in Practice: A Hermeneutic Phenomenological Study - Carruthers, Robyn (Auckland University of Technology, 2013)
Holism is a relatively common claim, used by many health professions; however it has a particular meaning within the natural medicine context, underpinning the core of its philosophy. Despite the crucial role of holism there is little research into how it manifests in natural medicine. This study explored natural health experience of ‘being holistic in practice’. A hermeneutic phenomenological methodology was used guided by the philosophies of Heidegger and Gadamer. Recruitment was initially via a purposive sampling method, inviting participants already known to me, and then using a snowballing technique, asking participants for further contacts. Prospective participants were contacted by email, outlining the research and giving them the opportunity to respond. The five participants in this study are professional naturopaths and/or medical herbalists who identify themselves as being holistic in practice and who are currently practising either full-time or part-time. Individual, semi-structured research conversations were carried out. Coherent stories were drawn from the verbatim transcripts, and analysed using interpretive phenomenological methods. The findings revealed how these practitioners carefully nurture their relationships with their clients, leading to the creation of a clearing or space for deeper communication. Specific embodied qualities of listening, allowing time, empathising and caring, sensing and knowing, being flexible, preparing and being authentic demonstrate a client-centred approach, all strongly underpinned by the core principles of the paradigm of natural medicine. This study shows the importance of natural health practitioners bringing these qualities into play within the therapeutic encounter. By implication, natural health education curricula ought to highlight ways of enabling students to learn and practise such complex qualities. It is through enacting intuitive embodied qualities, letting the clearing for deeper communication open up, that practitioners honour the principle of holism and guide their clients to explore their own health.
Keywords: CAM; Hermeneutic phenomenology; Herbal medicine; Being holistic; Clinical practice; Holism; Naturopathy